BUDAYA PATRIARKI DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL SAADAWI - Setyowati, Nurul Rahayu; Kasnadi; Hurustyanti, Hestri (STKIP PGRI Ponorogo Press, 2021)
This study aims to describe the forms of patriarchal culture and analyze the life of Firdaus figures in the middle of patriarchal culture. The theory used in this study is feminist literary theory. This qualitative research draws data sources from the novel Perempuan di Titik Nol by Nawal El Saadawi with library study techniques and analyzed by recording data, classifying data, analyzing based on feminism theory, presenting the results of analysis and drawing conclusions. The results of this study showed the representation of patriarchal cultural forms that are divided into domestic patriarchy and public patriarchy as well as data analysis based on the forms of patriarchal systems.